Analisis terhadap Tindak Pidana Penipuan Penjualan Mobil yang Dilakukan oleh Oknum Anggota Kepolisian Republik Indonesia - Fransiska Migiliani Jehula; Heryanto Amalo; Debi F. Ng.Fallo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to determine the application and considerations of criminal law to the criminal act of car sales fraud committed by members of the Indonesian National Police based on Decision Number 3/Pid.B/2024/Pn Rtg. The research method used is a normative research method. Normative research is a method that focuses on analysis that is conceptualized and developed by examining the rules, norms, and rules related to the problem being researched. The results of the study show that (1) the perpetrator of a crime committed by a member of the police who is a civil servant, the judge imposes a general crime but does not apply a code of ethics hearing, which should be subject to disciplinary sanctions and code of ethics sanctions. (2) The judge in considering a decision should pay close attention to the incriminating matter of the defendant, namely the defendant's actions that are contrary to his work as a law enforcer.